Spectroscopic, structural, electrochemical, and cytotoxicity studies on dithiocarbamato-chelated ruthenium organometallics incorporating imine-phenol function. Issue 1 (2nd January 2019) - Ghosh, Mrinal Kanti; Mandal, Suman; Mohapatra, Sudip; Chatterjee, Annesha; Bhattacharyya, Arindam; Chattopadhyay, Swarup
Abstract: The heterogeneous phase reaction of [Ru( η 2 -RL)(PPh3 )2 (CO)Cl] (1 ) with the sodium salts of dimethyl dithiocarbamate ( Me DTC), diethyl dithiocarbamate ( Et DTC), and pyrrolidine dithiocarbamate ( Pyr DTC) ligands led to the isolation of bright-yellow crystalline solids of type [Ru( η 1 -RL)(PPh3 )2 (CO)( R′ DTC)] (2 (R)( R′ DTC)) where η 2 -RL is C6 H2 O-2-CHNHC6 H4 R( p )-3-Me-5, η 1 -RL is C6 H2 OH-2-CHNC6 H4 R( p )-3-Me-5, R is Me, OMe, Cl, and R ′ = Me, Et, Pyr. The binding of dithiocarbamate ligand is accompanied by the dissociation of Ru-O and Ru-Cl bonds along with concomitant prototropic shift from iminium–phenolato to imine–phenol motif. The reaction also involves a sterically controlled change in rotational conformation in going to the products. The X-ray crystal structure of [Ru( η 1 -ClL)(PPh3 )2 (CO)( Et DTC)] (2 (Cl)( Et DTC)) has been described here. An account of different spectral (UV–Vis, IR, NMR) and electrochemical data of the complexes are also asserted. Density functional theory (DFT) and time-dependent density functional theory (TD-DFT) analyses were performed to scrutinize the electronic structure and the absorption spectra of the complexes. One of the dithiocarbamato complexes has also been found to have in vitro antiproliferative properties against MDA-MB-231 breast cancer cell line which was determined by MTT assay. Cell death occurs mainly through apoptosis and flow cytometric analysis indicates that the complex induces cell cycle arrest in the sub G0/G1 phase. GRAPHICAL ABSTRACT: